Encouraging Consumer Charitable Behavior: The Impact of Charitable Motivations, Gratitude, and Materialism - Bock, Dora E. (Journal of business ethics, 2018)
The United States is one of the most charitable nations, yet comprises some of the most materialistic citizens in the world. Interestingly, little is known about how the consumer trait of materialism, as well as the opposing moral trait of gratitude, influences charitable giving. We address this gap in the literature by theorizing and empirically testing that the effects of these consumer traits on charitable behavior can be explained by diverse motivations. We discuss the theoretical implications, along with implications for charitable organizations, and offer suggestions for future research.